Pengaruh profitabilitas dan struktur modal terhadap nilai perusahaan pada sektor transportasi - Oktrivina, Amelia; Astuti, Shinta Budi; Janah, Zulfa Nurul (LPMP Imperium, 2023)
This study aims to analyze the impact of profitability, measured by return on assets and equity, and capital structure assessed through the debt-to-equity ratio on firm value in the transportation sector listed on the Indonesia Stock Exchange. The sample consists of 13 companies over a research period from 2017 to 2020, utilizing purposive sampling for sample selection. A total of 52 observations were conducted, employing panel data analysis techniques with the assistance of Eviews 10 software. The results indicate that return on assets and return on equity do not affect firm value during the specified period. In contrast, the debt-to-equity ratio has a positive influence on firm value. Public interest statements This research highlights the importance of understanding factors influencing firm value, such as profitability and capital structure, for stakeholders in the transportation sector. This study offers insights that can aid investors and managers in making informed investment and financial management decisions. The findings are expected to contribute to developing better and more sustainable business practices within the transportation industry.